A Parody of Psalm 8 in Job 7:17-19 - Bernadus Dirgaprimawan (P3TK, Sanata Dharma University, 2018)
The book of Job presents us with a shocking story of a righteous man. He does everything what the Law says. Yet, he suffers. He looks for the answer of his suffering and finds nothing satisfactory. Uniquely, in chapter 7, the protagonist laments. The form of his lamentation somehow reminds its readers a poem similar to Psalm 8. However, there is a big contrast. Psalm 8 is a joyful hymn. Psalm 8 expresses mans confidence in Gods faithful love. Yet, Job 7 contains a distress of man who experiences God as a cruel watchman. He feels that his life is completely under Gods surveillance that makes him suffocated. Based on its literary genre, Job 7 is considered as a parody. Parody works by adapting a previously popular literary work into a new one, but with different intentions. In this paper, the intention of Jobs author is going to be examined. Through the short analysis of its literary form, what can be found is that the author of Job 7 purposefully conveys a sharp criticism to the general notion of the Wisdom Tradition of that era. The Wisdom Tradition emphasizes much on the faith in God based on the relation between punishment and reward. This emphasis has reduced the complexity of human suffering.